PROSPECTIVE STUDY OF QUALITY OF LIFE IN PATIENTS WITH MYOTONIC DYSTROPHY TYPE 2: Quality of life follow–up in myotonic dystrophy type 2 - Božović, Ivo; Ivana; Ivo; Palibrk, Aleksa; Kezic, Ivana; Ivanovic, Vukan; Lazovic, Jelena; Peric, Stojan (Medical Research, 2023)
Abstract Introduction /Aim: Although myotonic dystrophy type 2 (DM2) is generally milder than DM1, quality of life (QoL) seems to be similarly impaired in these two disorders. There are no studies that assessed QoL during the course of DM2. Our aim was to assess QoL and disease outcome in patients with DM2 after a five-year follow-up period. Material and Methods: Study originally comprised 49 DM2 patients at baseline. During five-year period, seven of them died, eight patients were lost to follow-up, one patient moved, and one refused testing. SF-36 and INQoL questionnaires were administered in 30 patients at baseline and at follow-up (47% males, 54±10 years old). Results: Patients who were retested had better RP and GH scores of the SF-36 and better weakness score of the INQoL compared to non-retested (p>0.05). After five-year follow-up, none of the SF-36 and INQoL scores differed compared to baseline (p>0.05). Conclusion: QoL did not change in DM2 patients during a five-year period, as measured by SF-36 and INQoL.